Brain tumours in children and adolescents may affect the circadian rhythm and quality of life. (14th September 2021) - Pickering, Line; Main, Katharina M.; Feldt‐Rasmussen, Ulla; Klose, Marianne; Sehested, Astrid; Mathiasen, René; Jennum, Poul
Abstract: Aim: Children with brain and cervical medulla tumours may experience circadian abnormalities and poor health. We aimed to examine their circadian rhythm, fatigue and quality of life (QoL). Methods: Children with a brain or cervical medulla tumour were recruited from the Paediatric Department, Rigshospitalet, Copenhagen, Denmark, between 2016 and 2020. They were grouped by tumour location involving the circadian regulatory system, defined as diencephalon, pineal gland, brain stem and cervical medulla, or other areas. Saliva melatonin and cortisol concentrations were measured. Sleep diaries and actigraphy assessed sleep‐wake patterns. The Pediatric Quality of Life Inventory, Multidimensional Fatigue Scale and Generic Core Scale measured fatigue and QoL. Results: We included 68 children (62% males) with a median age (25th‐75th percentiles) of 12.2 (7.7–16.3) years. Children with tumours involving the circadian regulatory system typically had a lower melatonin peak ( p =0.06) and experienced significantly more fatigue and poorer QoL. Low melatonin profiles were observed in 31% and 4% had a phase‐shifted daytime peak, compared with 14% and 0%, respectively, in children with tumours located elsewhere. Children with low melatonin profiles had significantly lower inter‐daily stability than those with normal profiles. Conclusion: Tumours involving the circadian regulatory system adversely affected circadian function, fatigue and QoL.